Effect of thrombin on calcium homeostasis in chick embryonic heart cells. Receptor-operated calcium entry with inositol trisphosphate and a pertussis toxin-sensitive G protein as second messengers. - Chien, W W (1990)
Thrombin increases intracellular calcium ([Ca++]i) in several cell types and causes a positive inotropic effect in the heart. We examined the mechanism of the thrombin-induced [Ca++]i increase in chick embryonic heart cells loaded with the fluorescent calcium indicator, indo-1. Thrombin (1 U/ml) increased both systolic and diastolic [Ca++]i from 617 +/- 62 and 324 +/- 46 to 1041 +/- 93 and 587 +/- 38 nM, respectively. An initial rapid [Ca++]i increase was followed by a more sustained increase. There were associated increases in contraction strength, beat frequency, and action potential duration. The [Ca++]i increase was not blocked by tetrodotoxin or verapamil, but was blocked by pretreatment with pertussis toxin (100 ng/ml). The thrombin-induced [Ca++]i increase was partly due to intracellular calcium release, since it persisted after removal of external calcium. The [Ca++]i increase in zero calcium was more transitory than in normal calcium and was potentiated by 10 mM Li+. Thrombin also induced influx of calcium across the surface membrane, which could be monitored using Mn++ ions, which quench indo-1 fluorescence when they enter the cell. Thrombin-induced Mn++ entry was insensitive to verapamil, but was blocked by 2 mM Ni++. Thrombin increased inositol trisphosphates by 180% at 90 s and this effect was also blocked by pretreatment with pertussis toxin. Conclusion: thrombin promotes calcium entry and release in embryonic heart cells even when action potentials are inhibited. Both modes of [Ca++]i increase may be coupled to the receptor by pertussis toxin-sensitive G proteins.